The Impact of the Promotion of Innovations on the Establishing of Industrial Concentrations (Clusters) in the Information Technology Sector in Bulgaria - Kotsev, Nikolai (Research Papers, 2014)
The paper explores the implementation of instruments for promotion of innovation for the development of clusters and cluster environment. The purpose is to determine the impact of OP “Competitiveness”, in the part directed to promotion of innovation and innovative environment, on the development of cluster environment, the IT sector in particular. The thesis is that OP “Competitiveness” provides conditions for the establishment of cluster environment in the IT sector, but not all of them.The IT sector is one of the main beneficiaries under the programme, one of the main suppliers to other beneficiaries and the leader in the field of created innovation through the programme. The sector restraints it interest from establishment of clusters, but a high concentration of IT companies in Sofia is observed.